The size of the industrial sector in Bazian district and its role in meeting the labor force : قەبارەى کەرتی پيشەسازى لە قەزای بازیاندا و ڕۆڵی لە دابینکردنی هەلی کاردا - Ali, Garmian H.; Saeed, Fuad Kh. (Humanities Journal of University of Zakho, 2024)
Abstract: The industrial composition in terms of size is responsible for the volume of employment in the industrial sector, which in turn affects the economy of a region or country, and because the Bazian district is characterized by being an industrial region, therefore this sector must play a role in providing job opportunities. Its industrial composition was classified into industries (small, medium, large) according to the Iraqi industrial classification according to employment،These sectors must be identified to make it easier for the researcher to address their impact on providing job opportunities. The problem of the study is that the researcher, as an individual in this field, noticed the presence of noticeable unemployment. This study aims to classify industrial activity and its distribution, as well as to study the quantitative and qualitative composition of workers in industrial units according to size and compare them to each other. An inductive approach and two types of methods were used (a descriptive method and an analytical method). In this study to reach a scientific conclusion, the number of workers in all industries in the region in late 2022 reached (6909) people, a percentage of (1.75%) of workers in small industries, (3.96%) of workers in medium industries, and (94.2%) of workers. In large industries. (1883) residents of the region work in industrial factories in the region, which is (27.23%) of the total number of workers in factories, and (2630) people outside the district from the population of Sulaymaniyah Governorate work in industrial factories, representing 38% of the total number of workers in industrial factories in the region. (2396) people from outside the Iraqi Kurdistan region work in industrial factories, representing (34.67%) of the total number of workers in industrial factories in the region.